2006
DOI: 10.2135/cropsci2005.06-0170
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chlorophyll Fluorescence Assessments to Differentiate Corn Hybrid Response To Variable Water Conditions

Abstract: Development of corn (Zea mays L.) germplasm tolerant to water stress will be vital to sustaining corn‐based farming in the U.S. Great Plains. In a companion 4‐yr field study near Shelton, NE, we found that 12 hybrids displayed differential agronomic responses to varying water levels, with tolerant hybrids yielding from 27 to 42% more than susceptible hybrids under stress while yielding similarly under no stress. The objective of this study was to determine if chlorophyll fluorescence (CF) measurements could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0
9

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 37 publications
9
61
0
9
Order By: Relevance
“…Therefore, these parameters might be used as a selection criterion for stalk productivity in sugarcane under drought stress. This is in accordance to Araus et al (1998), O'Neill et al (2006) and Rong-hua et al (2006) that worked with wheat, corn and barley, respectively.…”
Section: Screening For Drought Tolerance In Sugarcanesupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, these parameters might be used as a selection criterion for stalk productivity in sugarcane under drought stress. This is in accordance to Araus et al (1998), O'Neill et al (2006) and Rong-hua et al (2006) that worked with wheat, corn and barley, respectively.…”
Section: Screening For Drought Tolerance In Sugarcanesupporting
confidence: 90%
“…the consequences of drought stress that may result from sustained photoinhibition and photo-bleaching (Long et al, 1994), and even though other plant processes, such as cell division and cell expansion are the earliest to respond to water deficit stress (Dale, 1988), a decline in SPAD index is a sensitive and readily measurable trait that could be used to screen for stress tolerance (O'Neill et al, 2006). The distribution of SPAD index values among the sugarcane genotypes used in this study is consistent with their tolerance-susceptibility classification, with the exception of the genotype TCP02-4587 at 90 DAT.…”
Section: Screening For Drought Tolerance In Sugarcanementioning
confidence: 99%
See 2 more Smart Citations
“…2d). O'Neill et al (2006) suggested that ΦPSII measurements can be used to distinguish tolerant from susceptible corn hybrids under drought conditions. Our results indicated that changes in ΦPSII during development of water stress (Fig.…”
Section: Discussionmentioning
confidence: 99%